SEPAK TERJANG ADE MOELYANA DALAM MERINTIS SENI LUKIS DARI LIMBAH PELEPAH PISANG DI CIMAHI TAHUN 1969-2010 - Junia Triani; Murdiyah Winarti; Moch Eryk Kamsori (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This study aims to explain the Ade Moelyana struggle’s in developing the art painting of wasted banana stalks in Cimahi from 1969 to 2010. The main issue discussed was “How was the Developments Art Painting of Wasted Banana Stalks in Cimahi from 1969-2010?”. The method used is the historical method through four phases of heuristics, criticism, interpretation and historiography. Based on the research results, the art painting of wasted banana stalks has existed since 1969. It is Ade Moelyana, a painter who introduced art painting of wasted banana stalks in Cimahi. In its development, this painting has been through the ups and downs, in early 1969, this painting was not accepted by most people in Cimahi even this painting is considered as junk. Then in the year 2000, the painting is experiencing the peak of development. This is because not only do marketing painting around Cimahi but abroad as well. Painting of wasted banana stalks can be used as a creative economic sector and creates jobs. Lack of awareness of the various parties to make this painting became dormant.